KEPEMIMPINAN DAKWAH: PERAN PARTISIPATIF DAN KOLABORATIF - Nabiel Al Musawa; Zamakhsyari Abdul Majid; Nurfitria Farhana; Siti Nuri Nurhaidah; Miftahussaadah Miftahussaadah; Khaeiruddin Khaeiruddin (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
This paper discusses the importance of the role of leaders in da'wah activities, especially in the context of participatory and collaborative da'wah. Leadership in da'wah not only involves the ability to lead and direct, but also demands skills in building communication, managing collaboration, and embracing active participation from various elements of society. Effective da'wah leaders are those who are able to build harmonious relationships, inspire engagement, and encourage constructive cooperation to achieve da'wah goals. The paper also analyzes several examples of successful da'wah leadership, identifies key factors that influence their success, and offers recommendations for leadership development in da'wah.